2019
DOI: 10.1038/s41598-019-49663-3
|View full text |Cite
|
Sign up to set email alerts
|

Rrm2b deletion causes mitochondrial metabolic defects in renal tubules

Abstract: Renal diseases impose considerable health and economic burdens on health systems worldwide, and there is a lack of efficient methods for the prevention and treatment due to their complexity and heterogeneity. Kidneys are organs with a high demand for energy produced by mitochondria, in which Rrm2b has critical functions as reported. The Rrm2b kidney-specific knockout mice we generated exhibited age-dependent exacerbated features, including mitochondrial dysfunction and increased oxidative stress; additionally,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…B6.Cg-Tg(ACTA1-cre)79Jme/J (stock number: 006149) and B6.CgPax7 tm1(cre/ERT2)Gaka /J mice (stock number: 017763) were purchased from The Jackson Laboratory. Rrm2b-floxed mice (Rrm2b F/F, Dr. Yun Yen Laboratory, City of Hope, US) 14 were crossed with either Pax7 Cre-ERT2 mice or HSA Cre mice to generate Rrm2b myofiber-specific knockout (Rrm2b F/F; HSA-Cre, smKO) or satellite cell-specific knockout (Rrm2b F/F; Pax7-Cre ERT2 , scKO) mice. Gt(ROSA)26Sor tm4(ACTBtdTomato,EGFP)Luo /J (ROSA mT/mG , stock number: 003474) mice were purchased from The Jackson Laboratory.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…B6.Cg-Tg(ACTA1-cre)79Jme/J (stock number: 006149) and B6.CgPax7 tm1(cre/ERT2)Gaka /J mice (stock number: 017763) were purchased from The Jackson Laboratory. Rrm2b-floxed mice (Rrm2b F/F, Dr. Yun Yen Laboratory, City of Hope, US) 14 were crossed with either Pax7 Cre-ERT2 mice or HSA Cre mice to generate Rrm2b myofiber-specific knockout (Rrm2b F/F; HSA-Cre, smKO) or satellite cell-specific knockout (Rrm2b F/F; Pax7-Cre ERT2 , scKO) mice. Gt(ROSA)26Sor tm4(ACTBtdTomato,EGFP)Luo /J (ROSA mT/mG , stock number: 003474) mice were purchased from The Jackson Laboratory.…”
Section: Methodsmentioning
confidence: 99%
“…The Rrm2b smKO mice might be a disease model for mitochondrial myopathy Our previous reports indicated that Rrm2b is involved in maintaining the dNTP pool, inhibiting oxidative stress, and modulating mitochondrial metabolism 14 . Patients with myopathy were found to have genetic defects in RRM2B and decreased RRM2B expression 16 .…”
Section: Signals From the Niche Control The Stemness Of Muscsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many clinical reports show that mutation of RRM2B causes myopathy, lactic acidosis, and ultimately death usually in infancy or early childhood (Finsterer & Zarrouk‐Mahjoub, 2018; Keshavan et al, 2020; Kropach et al, 2017; Penque et al, 2019). In these patients, the mutation of RRM2B leads to MDMDs with insufficient mtDNA; therefore, inadequate mitochondrial activity crippled cells demanding high energy such as muscle and renal cells (Chen et al, 2019; El‐Hattab et al, 2017). In contrast to mammals, the major fetal energy in oviparous animals depends on the yolk.…”
Section: Resultsmentioning
confidence: 99%
“…Though the two mitochondrial rRNAs and 22 mitochondrial tRNAs are not mentioned in MitoCarta2.0 due to their nonprotein-coding properties, they also have a mitochondrial localization. No standardized definitions exist on whether gene products have to be located within the mitochondrion, on the mitochondrial membrane and responsible for the mitochondrial transport, or outside the mitochondrion and responsible for the mitochondrial metabolism, such as RRM2B (Bourdon et al, 2007;Chen et al, 2019). For instance, defects in the cytosolic tRNA synthetase IARS, necessary for the synthesis of nuclear-encoded mitochondrial proteins, are not regarded as a cause of primary mitochondrial disease, despite the fact of being associated with an OXPHOS defect (Kopajtich et al, 2016).…”
Section: Definition Of Mitochondrial Disease Genesmentioning
confidence: 99%